On regularity, transitivity, and ergodic principle for quadratic stochastic volterra operators - Saburov, Mansoor (O'zbekistan Fanlar Akademiyasi, 2012)
In this paper we showed an equivalence of notions of regularity, transitivity and Ergodic principle for quadratic stochastic Volterra operators acting on the finite dimensional simplex.